2001
DOI: 10.1111/j.1365-2621.2001.tb11328.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maitake (Grifola frondosa) Mushroom Powder on Bread Properties

Abstract: Maitake mushroom powder drastically decreased dough strength in Brabender farinography and was also effective in deteriorating bread-making properties (bread height and specific volume). These effects of maitake on farinograph values and bread-making properties were lost by boiling maitake/water suspensions or by adding EDTA, suggesting that the deteriorative effects by maitake may be caused by a metal protease. Flour dough that contained maitake was treated with 1% sodium dodecyl sulfate (SDS), and extracted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 9 publications
4
20
1
1
Order By: Relevance
“…The column was equilibrated with I % SDS, and the proteins were eluted from the column with 1% SDS. As previously reported (Seguchi et al, 2001), three main protein peaks, H (High) MW I, M (Medium) MW II, and L (Low) MW III appeared and in flour the peak heights were almost the same (Fig. 3-1-A and Table 3).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The column was equilibrated with I % SDS, and the proteins were eluted from the column with 1% SDS. As previously reported (Seguchi et al, 2001), three main protein peaks, H (High) MW I, M (Medium) MW II, and L (Low) MW III appeared and in flour the peak heights were almost the same (Fig. 3-1-A and Table 3).…”
Section: Resultssupporting
confidence: 84%
“…Extracted proteins were dialyzed against water and freeze dried. Size-exclusion high-performance liquid chromatography (SE-HPLC) of proteins from those flours was performed according to Seguchi et al (2001). For SE-HPLC analysis at 280 nm, a Shimadzu liquid chromatograph LC-3A connected to a Shodex Protein KW 803 column (5009010) was used.…”
Section: Brabenderfarinograph and Breadmaking Test Leekmentioning
confidence: 99%
“…These findings were similar to those of Gatta and Piergiovanni (1996) who reported specific volume of 1.5 cm 3 /g for bread containing 20% sunflower meal. Other studies have reported higher specific volumes such as: 3.7-4.6 cm 3 /g for wheat breads with hydrocolloids (Ba´rcenas, Benedito, & Rosell, 2004); 3.3-4.0 cm 3 /g for breads prepared with unheated maitake mushroom powder (Seguchi, Morimoto, Abe, & Yoshino, 2001); and 3.4-4.4 cm 3 /g in wheat breads with dextrins (Miyazaki et al, 2004) for breads than the present study.…”
Section: Physical Propertiescontrasting
confidence: 51%
“…In the available literature, there are data about the dough rheology and bread properties when wheat flour was supplemented with some mushroom flour, but no data about the effect of Boletus edulis on these properties. Thus, the investigation of the effect of maitake (Grifiola frondosa), mushroom powder on bread properties showed that the mushroom powder drastically decreased the dough strength [22] and had the effect on deteriorating the bread properties such as the bread height and a specific volume. Hong et al (2005) [23] reported that the final viscosities decreased by increasing the amount of the oyster mushroom (Pleurotus ostreatus) powder to the wheat flour.…”
Section: Introductionmentioning
confidence: 99%